STRATEGI PEMASARAN SEKOLAH SWASTA DALAM MEMBANGUN CITRA POSITIF MASYARAKAT - Juan Ferdiana; Achmad Supriyanto; Raden Bambang Sumarsono; Asep Sunandar; Juan Ferdiana; Achmad Supriyanto; Raden Bambang Sumarsono (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: The goal of this study is to describe in detail the activities of private-schoolmarketing strategies in establishing a positive image of society that starts at thestage of private school's efforts to build positive image of people, marketing shapes,contributing factors, obstacles and solutions to school strategies in building apositive image of society. The study is done by a qualitative approach using the typeof case study and researchers as a data collector. Data collection techniques aredone through interviews, observation, and documentation. Data analysis is done bymatching patterns. The data reduction techniques used in this study are degrees oftrust, degrees of computing, degrees of dependability, and degrees of certainty. Thestudy was: (1) the headmaster's efforts to build a positive image of society throughinnovative new programs, among other things. Excursion study program, andachievement. (2) marketing forms are made available through websites andyoutube. Next, at the time of the administration of the GDP forms, through flyers,pamphlets, and banners. (3) the insan amanah primary factor is divided into two.Internal and external factors. (4) school strategy constraints from time spentbetween school parties and parents or other instations. The solution would be toreschedule themeeting between.